Dynamic Research of a Nonlinear Stochastic Vibratory Machine - Yimin Zhang; Qiaoling Liu; Bangchun Wen (Shock and Vibration)
This paper presents the dynamics problems of stochastic vibratory machine systems. The random responses of the vibratory machine systems with stochastic parameters subjected to random excitation are researched using a stochastic perturbation method. The numerical results are obtained. The dynamic characteristics of nonlinear stochastic vibratory machine are analyzed.